FICTION-TSA analysis of the B-cell compartment in myeloma shows no significant expansion of myeloma precursor cells - Davies, F.E; Rawstron, A.C; Pratt, G.; O'Connor, S.; Su'ut, L.; Blythe, D.; Fenton, J.; Claydon, D.; Child, J.A; Jack, A.S; Morgan, G.J. (British Journal of Haematology, 1999)
Faith E. Davies, Andrew C. Rawstron, Guy Pratt, Sheila O'Connor, Lela Su'ut, David Blythe, James Fenton, David Claydon, J. Anthony Child, Andrew S. Jack & Gareth J. Morgan